ANIMATED CHARACTERS OF SASA AND WIWIT IN PUBLIC SERVICE ADVERTISEMENTS AS INFORMATION ON THE BENEFITS OF OIL PALM BY BPDPKS (PALM PLANTATION FUND MANAGEMENT AGENCY) - Renita, Dessy Tasya; Isfiaty, Tiara (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Palm oil is an important industrial crop as a source of cooking oil, industrial oil and fuel. Indonesia, as the world’s largest producer, plays a strategic role in the global economy with the palm oil sector providing millions of jobs. However, smear campaigns regarding palm oil from other countries have become a controversial issue. The Palm Oil Plantation Fund Management Agency (BPDPKS) plays a role in spreading positive information about palm oil, including through public service advertisements that use 2D animation. In this advertisement, the characters Sasa and Wiwit are used as icons to convey information about the benefits of palm oil to the public. This research aims to analyze the animated characters Sasa and Wiwit in BPDPKS Public Service Advertisements which use 2D animation. This analysis is important to understand how an animated character can convey an effective message or information to the public.